Endothelin antagonism and sodium glucose Co-transporter 2 inhibition. A potential combination therapeutic strategy for COVID-19. (August 2021) - Fisk, Marie; Althage, Magnus; Moosmang, Sven; Greasley, Peter J.; Cope, Andrew P.; Jayne, David RW.; Galloway, James; Hall, Frances; Wilkinson, Ian B.; Ambery, Philip; Cheriyan, Joseph
Abstract: The novel coronavirus 2019 (COVID-19) infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a global pandemic that requires a multi-faceted approach to tackle this unprecedent health crisis. Therapeutics to treat COVID-19 are an integral part of any such management strategy and there is a substantial unmet need for treatments for individuals most at risk of severe disease. This perspective review provides rationale of a combined therapeutic regimen of selective endothelin-A (ET-A) receptor antagonism and sodium glucose co-transporter-2 (SGLT-2) inhibition to treat COVID-19. Endothelin is a potent vasoconstrictor with pro-inflammatory and atherosclerotic effects. It is upregulated in a number of conditions including acute respiratory distress syndrome and cardiovascular disease. Endothelin mediates vasocontractility via endothelin (ET-A and ET-B) receptors on vascular smooth muscle cells (VSMCs). ET-B receptors regulate endothelin clearance and are present on endothelial cells, where in contrast to their role on VSMCs, mediate vasodilation. Therefore, selective endothelin-A (ET-A) receptor inhibition is likely the optimal approach to attenuate the injurious effects of endothelin and may reduce ventilation-perfusion mismatch and pulmonary inflammation, whilst improving pulmonary haemodynamics and oxygenation. SGLT-2 inhibition may dampen inflammatory cytokines, reduce hyperglycaemia if present, improve endothelial function, cardiovascular haemodynamics and cellular bioenergetics. This combination therapeutic approach may therefore have beneficial effects to mitigate both the pulmonary, metabolic and cardiorenal manifestations of COVID-19. Given these drug classes include medicines licensed to treat heart failure, diabetes and pulmonary hypertension respectively, information regarding their safety profile is established. Randomised controlled clinical trials are the best way to determine efficacy and safety of these medicines in COVID-19.